Multichannel Fluorescence Microscopy: Advantages of Going beyond a Single Emission. Issue 5 (5th January 2022) - Rodríguez-Sevilla, Paloma; Thompson, Sebastian A.; Jaque, Daniel
Abstract : Fluorescent microscopy has enabled the study of intracellular processes and revealed the most intricate details of the subcellular structure. This has benefitted not only the basic biological science, but also has had an impact in numerous biomedical applications. Basic fluorescent sensing techniques use the change in the absolute emission of a fluorescent sensor. This entails some disadvantages as the signal might be influenced by factors not directly related to the process under study (e.g., fluctuations in the excitation source). To overcome these drawbacks, one can use multiple emissions of a single or various fluorophores. There are numerous examples of multichannel fluorescence microscopy techniques that have given rise to numerous ratiometric methods and multiplexing assays. Herein, how the use of multiple emission channels has impacted fluorescence microscopy in terms of speed, sensitivity, and resolution is reviewed. Using recent examples, how the easy implementation of multichannel detection can overcome current limitations of the main used fluorescence techniques and promote the development of novel microscopy methods is shown. Abstract : Cellular imaging and sensing have greatly befitted from fluorescent microscopy enabled by fluorescent markers. However, regular absolute single emission techniques present some drawbacks that affect their reliability. As discussed here, the use of multiple emissions can help to overcome these disadvantages to increase the speed and versatility, reduce the complexity, and improve the sensitivity and resolution of fluorescence microscopy techniques.